2021
DOI: 10.3390/pathogens10040482
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Typing of Listeria monocytogenes IVb Serogroup Isolated from Food and Food Production Environments in Poland

Abstract: Listeria monocytogenes is one of the most important foodborne pathogens that may be present in food and in food processing environments. In the present study, 91 L. monocytogenes isolates of serogroup IVb from raw meat, ready-to-eat food and food production environments in Poland were characterized by whole genome sequencing (WGS). The strains were also compared, using core genome multi-locus sequence typing (cgMLST) analysis, with 186 genomes of L. monocytogenes recovered worldwide from food, environments, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 68 publications
4
11
0
Order By: Relevance
“…Serogroup IVb was found to be more prevalent than IIa among wildlife animal samples in Spain [41]. Hypervirulent clones of IVb were present in food and food production environments, highlighting their importance associated with human invasive listeriosis cases [42]. In our dataset, CC1 in the context of abortion was not observed at all, and neurological manifestations of listeriosis in cattle in Latvia are rarely reported, only one case since 2013, and in that case, we identified L. monocytogenes ST1 (CC1) (unpublished data, BIOR).…”
Section: Discussionmentioning
confidence: 95%
“…Serogroup IVb was found to be more prevalent than IIa among wildlife animal samples in Spain [41]. Hypervirulent clones of IVb were present in food and food production environments, highlighting their importance associated with human invasive listeriosis cases [42]. In our dataset, CC1 in the context of abortion was not observed at all, and neurological manifestations of listeriosis in cattle in Latvia are rarely reported, only one case since 2013, and in that case, we identified L. monocytogenes ST1 (CC1) (unpublished data, BIOR).…”
Section: Discussionmentioning
confidence: 95%
“…In this study, CC1, CC2, CC4, and CC6 made up 66.7% of lineage I isolates and were isolated from food, FPEs, and animals, as well as from human cases. This result is similar to that reported in Lachtara et al (2021) on the prevalence of CC1, CC2, and CC6 in food and FPE isolates in Poland. These CCs have previously been described as hypervirulent (Maury et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, L. monocytogenes serogroup IVb, CC2/ST2 was the isolates most frequently detected from drains (FSOpA and B). Similarly, the same molecular variant was predominant in an analysis performed in Poland in a study monitoring RTE foods, meat, and food environments [ 80 ]. It has also been reported that CC2 isolates were more salt-tolerant than isolates belonging to other CCs [ 81 ].…”
Section: Discussionmentioning
confidence: 99%